ANALISIS TINGKAT KESEHATAN PERUSAHAAN BERDASARKAN KEPUTUSAN MENTERI BUMN NOMOR : KEP-100/MBU/2002 ( Studi Kasus Pada PT Pegadaian Blimbing Malang Periode 2015 – 2017 ) - PRASETYA, FERDIAN NENDRA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims at determining the health level of a state-owned enterprise (SOE), i.e. PT Pegadaian Blimbing 2015-2017, in terms of the financial, operational, and administrative aspects on the basis of the Decree of Indonesian Minister for SOE Number: KEP-100/MBU/2002. The financial aspect is assessed using the size of financial ratios, the operational aspect is examined on the account of the most dominant operations, and the administrative one is viewed through timeliness of the financial reporting and partnership program. The primary data of this quantitative research are collected by interviews and financial reports. The assessment outcome on the health categories is classified in accordance with the scores obtained: AAA if the score is more than 95, AA if the score lies between 80 to 95, and A if the score is less than eighty and more than 65. The results of the study show that Pegadaian scored 80.5 (category AA, appreciated as health) in2015, earned 82.5 (category AA, appreciated as health) in 2016, and got 79 (category A, appreciated as health) in 2017.Â Keywords: Health Level, State-Owned Enterprise, Financial Aspect, Operational Aspect, Administrative Aspect, Financial Performance.